Description of two new Discocelis species (Polycladida: Acotylea: Discocelidae) from the Persian Gulf with a review of the genus - Maghsoudlou, Abdolvahab; Rahimian, Hassan (Zootaxa, 2013)
Two new polyclad species, from northern intertidal zone and shallow rocky shores of the Persian Gulf, Discocelis persica sp. nov. and Discocelis hollemani sp. nov., are described. D. persica possesses a thick and broadly oval body tapering somewhat posteriorly, without any obvious color pattern; with marginal eyes extended around the anterior margin of the body; cerebral eyes forming two clusters, each further subdivided into anterior and posterior groups, about 100 eyespots at the anterior group and 55 eyespots at the posterior groups; mouth at the posterior end of the pharynx; male atrium with three to four distinct lobes, with numerous prostatoid organs of two distinct sizes, without villus-like projections; and with a horseshoe-shaped Lang’s vesicle. D. hollemani characterized by a thick and broadly oval body, not tapering antro-pos-teriorly, without any obvious color pattern; marginal eyes extended to the vicinity of the posterior end of pharynx; the ce-rebral eyes forming two clusters, each further subdivided into anterior and posterior groups in relation to the cerebral organ, about 50 eyespots at the anterior group and 20 eyespots at the posterior groups; mouth at the posterior end of the pharynx; the male atrium with two distinct lobes, with numerous prostatoids of two distinct sizes and different contents; villus-like projections absent, and with a horseshoe-shaped Lang’s vesicle.